Emerging topics in scientific research on global water-use efficiency - Aleixandre-Tudó, J. L.; Castelló-Cogollos, L.; Aleixandre, J. L.; Aleixandre-Benavent, R. (The Journal of agricultural science, 2019)
A bibliometric analysis of research articles published on water-use efficiency was performed using the Web of Science database and evaluated. Journal titles, publication years, subject categories, keywords and countries publishing were obtained. A number of 2077 papers were retrieved, two-thirds of them published in the last decade. The articles were published in 439 journals, with Agricultural Water Management , Agronomy Journal, Crop Science, Field Crops Research and Indian Journal of Agricultural Sciences the most productive. Most of the leading productive journals have Impact Factors in the top quartiles of the Journal Citation Reports. Agronomy, Plant Sciences, Water Resources and Agriculture Multidisciplinary were the most common journal subject categories, indicating a wide diversity of research fields ascribed to this topic. The predominant key words and phrases used were growth, ‘carbon isotope discrimination’, yield, photosynthesis, ‘gas exchange’, evapotranspiration and ‘stomatal conductance’. The productivity ranking for countries was headed by China (456 papers), followed by the USA (410), Australia (176) and India (165). A content analysis of the papers made identification of the key issues of greatest scientific concern possible, as well as their evolution over time. The most cited papers relate to physiological aspects, but also important studies on experimental biology, drought resistance, effects of climate, crop production and ecology, among others.